Day-to-Day Mobility, Affect, and Stress Couplings in Swiss Older Adults. (17th December 2021) - Roecke, Christina; Kim, Eun-Kyeong; Griffel, Pascal; Moulder, Robert; Fu, Cheng; Luo, Minxia; Martin, Mike; Weibel, Robert
Abstract: The Mobility, Activity, and Social Interactions Study (MOASIS) is part of a global effort to more closely examine indicators of functional ability in relation to person characteristics and life contexts as proposed by the WHO's healthy aging definition. In MOASIS, sensor-based and self-reported mobility and activity indicators were used to capture functional ability in 153 community-dwelling older adults aged 65-91 over 30 days. The present study examines daily time out-of-home and place diversity and its within-person associations with positive and negative affect and stress. Initial between-person analyses indicate that mobility is only weakly related to indicators of physical and mental health. We propose that the health- and well-being implications of mobility more strongly play out in daily life and at the within-person level, and will examine general health, cognitive ability, and marital status as intrinsic capacity moderators accounting for some of the expected interindividual heterogeneity.